Learning from home environment: Academic writing course for EFL undergraduates through Google Classroom application - Amrina Rosyada; Hanna Sundari (Studies in English Language and Education, 2021)
Learning academic writing seems to be a great challenge for most English as a Foreign Language (EFL) students in non-native English-speaking countries, including in Indonesia. During the COVID-19 pandemic, the issue appears to be more challenging where teachers are persuaded to learn from their home environment (LHE). Several online applications are freely available, and one of the most common applications is Google Classroom. However, the use of such application towards the students’ performance and perception remains understudied. This research aimed at exploring the practices of Google Classroom in facilitating the Academic Writing course of EFL undergraduates. Engaged by 96 participants of third-year students in the English Education Program, the research conducted an explanatory sequential research design by correlating the results data on writing assignments and a set of questionnaires. The findings indicated a significant correlation between using Google Classroom and the students’ writing performance. Moreover, most students expressed their satisfaction with Google Classroom’s practical features to get involved in the academic writing course. The students were satisfied with Google Classroom’s features that were easy to be recognized and easy to be operated. The Google Classroom features also provide clear instructions, practical directions, and the most valuable feature, that is assignment reminders for the students. It can be said that using Google Classroom in the EFL academic writing course at higher education is a great experience and brings great advantages to students’ outcomes.